THE ROLE OF JOB SATISFACTION IN MEDIATING THE EFFECT OF COMPENSATION AND LEADERSHIP ON EMPLOYEE PERFORMANCE AT THE FACULTY OF AGRICULTURE, METHODIST UNIVERSITY OF INDONESIA - Gunawan Sagala; Sofyan Matondang; Jeudi Agustina T.P Sianturi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the role of job satisfaction as a mediating variable in the relationship between compensation and leadership on employee performance at the Faculty of Agriculture, Universitas Methodist Indonesia. The research uses a quantitative approach with a survey method, where the entire population of employees is selected as the sample through a census technique. Data were collected using structured questionnaires and analyzed using multiple regression analysis along with mediation testing through the Sobel test. The results indicate that compensation has a positive and significant effect on employee performance, and leadership also shows a positive and significant influence on employee performance. In addition, both compensation and leadership significantly affect job satisfaction. The mediation test results reveal that job satisfaction is able to mediate the relationship between compensation and employee performance as well as between leadership and employee performance. Furthermore, job satisfaction itself has a positive and significant effect on employee performance. These findings imply that improving employee performance can be effectively achieved through the provision of fair compensation, the implementation of effective leadership, and the enhancement of job satisfaction. Therefore, organizations are expected to manage these three factors simultaneously in order to create optimal employee performance and organizational outcomes.